Proteomics Investigation of the Time Course Responses of RAW264.7 Macrophages to Infections With the Wild-Type and Twin-Arginine Translocation Mutant Strains of Brucella melitensis - Yan, Xin; Hu, Sen; Yang, Yan; Xu, Da; Liu, Wenxing; Li, Ganwu; Cai, Wentong; Bu, Zhigao (Frontiers in Cellular and Infection Microbiology, 2021)
Brucella, a notorious intracellular pathogen, causes chronic infections in many mammals, including humans. The twin-arginine translocation (Tat) pathway transports folded proteins across the cytoplasmic membrane; protein substrates translocated by Brucella include ABC transporters, oxidoreductases, and cell envelope biosynthesis proteins. Previously, we showed that a Tat mutant of Brucella melitensis M28 exhibits reduced survival within murine macrophages. In this study, we compared the host responses elicited by wild-type M28 and its Tat-mutant strains ex vivo. We utilized label-free quantitative proteomics to assess proteomic changes in RAW264.7 macrophages after infection with M28 and its Tat mutants. A total of 6085 macrophage proteins were identified with high confidence, and 79, 50, and 99 proteins were differentially produced upon infection with the Tat mutant at 4, 24, and 48 hpi, respectively, relative to the wild-type infection. Gene ontology and KEGG enrichment analysis indicated that immune response-related proteins were enriched among the upregulated proteins. Compared to the wild-type M28 infection, the most upregulated proteins upon Tat-mutant infection included the cytosolic nucleic acid signaling pathway-related proteins IFIH1, DHX58, IFI202, IFI204, and ISG15 and the NF-κB signaling pathway-related proteins PTGS2, CD40, and TRAF1, suggesting that the host increases the production of these proteins in response to Tat mutant infection. Upregulation of some proteins was further verified by a parallel reaction monitoring (PRM) assay. ELISA and qRT-PCR assays indicated that Tat mutant infection significantly induced proinflammatory cytokine (TNF-α and IL-6) and nitric oxide (NO) production. Finally, we showed that the Tat mutant displays higher sensitivity to nitrosative stress than the wild type and that treatment with the NO synthase inhibitor L-NMMA significantly increases the intracellular survival of the Tat mutant, indicating that NO production contributes to restricting Tat mutant survival within macrophages. Collectively, this work improves our understanding of host immune responses to Tat mutants and provides insights into the mechanisms underlying the attenuated virulence of Tat mutants.